Implementation of Group Counseling Services Using Discussion Techniques to Increase Student Learning Motivation - Bagus Amirullah; Syifaurrahmah (Penerbit Hellow Pustaka, 2024)
This research is a qualitative study. Data collection was carried out using observation, interview and documentation methods. The data analysis used is triangulation. This research aims to: 1. find out the application of group counseling using discussion techniques to increase learning motivation given to class VIIIB Madrasah Tsanawiyah An-Najah 1 Karduluk Pragaan Sumenep students. 2. to find out the impact of the group counseling process with discussion techniques in increasing learning motivation for class VIII B Madrasah Tsanawiyah An-Najah 1 Karduluk Pragaan Sumenep students. The research result is that the implementation of group counseling services using discussion techniques provided to class VIII B students at Madrasah Tsanawiyah An-Najah 1 Karduluk Pragaan Sumenep has been carried out well, carried out regularly once a month involving all class VIII B students, apart from being carried out in an official discussion forum (room) guidance counseling using this discussion technique is also sometimes carried out outside the room, in the form of casual conversations with students. The impact of group counseling services with discussion techniques in increasing learning motivation for class VIII B Madrasah Tsanawiyah An-Najah 1 Karduluk Pragaan Sumenep students is: a. Class VIII B students at Madrasah Tsanawiyah An-Najah 1 from the start lacked enthusiasm for learning and were often indifferent to learning by carrying out group counseling using discussion techniques and seemed more enthusiastic when carrying out discussions, because teachers in carrying out discussions often gave rewards to discussion participants, either in the form of praise or small gifts that can attract students' enthusiasm for active learning. b. Class VIII B An-Najah 1 students appear to be increasingly motivated to learn and hone their knowledge by discussing, because teachers as facilitators try to instill a sense of mutual respect between fellow students.